A Chinese Girl With LIG4 Syndrome and Hematopoietic Stem Cell Transplantation: A Rare Case Report and Review of the Literature - Chenjia Jiang; Wenyang Wang; Yazhou Li; Xiwang Liu; Zhirui Zhu (Clinical Case Reports)
ABSTRACT LIG4 syndrome is an exceptionally rare primary immune deficiency. It is an autosomal recessive genetic disease, falling within the spectrum of genetic disorders characterized by impaired DNA damage response mechanisms. Common clinical characteristics encompass microcephaly, growth retardation, developmental delays, facial deformities, variable immune deficiencies, pancytopenia, heightened susceptibility to malignant tumors, and significant clinical and cellular radiosensitivity. Hematopoietic stem cell transplantation (HSCT) is a curative treatment for LIG4 syndrome and may mitigate the long‐term risk of developing lymphoid malignancies by improving tumor surveillance.